2015
DOI: 10.1177/1098300715596134
|View full text |Cite
|
Sign up to set email alerts
|

Self-Monitoring for High School Students With Disabilities

Abstract: Self-monitoring interventions are well supported within the empirical literature as improving classroom engagement for students with disabilities. However, studies implementing self-monitoring interventions in high school settings are rarely conducted despite their potential to improve student academic and behavioral outcomes. In an investigation of an unobtrusive, self-monitoring application loaded on a handheld device, classroom engagement and perceived academic benefits were assessed in a withdrawal design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 31 publications
3
47
0
Order By: Relevance
“…Eighteen of the 19 studies reported participant gender. Of the 29 participants, 26 were male (83.9%; Agran et al, 2005;Cihak et al, 2010;Clemons, et al, 2016;Coyle & Cole, 2004;Crutchfield, et al, 2015;Ganz & Sigafoos, 2005;Hughes, et al, 2002;Legge et al, 2010;Rock, 2005;Rouse et al, 2014;Soares et al, 2009;State & Kern, 2012;Tiger et al, 2009) and only four were female (9.6%; Bouck et al, 2014;Mancina et al, 2000;Morrison et al, 2001;Rock & Thead, 2007). Koegel and Koegel (1990) did not specify the genders of the four participants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eighteen of the 19 studies reported participant gender. Of the 29 participants, 26 were male (83.9%; Agran et al, 2005;Cihak et al, 2010;Clemons, et al, 2016;Coyle & Cole, 2004;Crutchfield, et al, 2015;Ganz & Sigafoos, 2005;Hughes, et al, 2002;Legge et al, 2010;Rock, 2005;Rouse et al, 2014;Soares et al, 2009;State & Kern, 2012;Tiger et al, 2009) and only four were female (9.6%; Bouck et al, 2014;Mancina et al, 2000;Morrison et al, 2001;Rock & Thead, 2007). Koegel and Koegel (1990) did not specify the genders of the four participants.…”
Section: Resultsmentioning
confidence: 99%
“…Settings included general education classrooms, special education classrooms, and alternative settings. General education was the most frequently utilized (42.1%) setting for implementing self-monitoring in the reviewed studies (Agran et al, 2005;Cihak et al, 2010;Clemons, et al, 2016;Hughes, et al, 2002;Morrison et al, 2001;Rock, 2005;Rock & Thead, 2007;State & Kern, 2012). Six studies were implemented in special education classrooms (31.6%%; Bouck et al, 2014;Coyle & Cole, 2004;Crutchfield, et al, 2015;Legge et al, 2010;Mancina, et al, 2000;Rouse et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations